A retrospective observational research study to describe the real‐world use of bosutinib in patients with chronic myeloid leukemia in the United Kingdom and the Netherlands. (17th May 2022) - Claudiani, Simone; Janssen, Jeroen J. W. M.; Byrne, Jenny; Smith, Graeme; Blijlevens, Nicole; Raghavan, Manoj; Smith, Matthew; Clark, Richard E.; Mclain‐Smith, Susan; Carter, Angela M.; Milojkovic, Dragana; Apperley, Jane F.
Abstract: Objectives: To describe the real‐world effectiveness and safety of bosutinib in patients with chronic myeloid leukemia (CML). Methods: This was a multi‐center, retrospective, non‐interventional chart review study conducted in 10 hospitals in the United Kingdom and the Netherlands. Results: Eighty‐seven patients were included. Bosutinib was the third‐line tyrosine kinase inhibitor (TKI) in 33 (38%) and fourth‐line in 44 (51%) patients. Median treatment duration was 15.6 months. Among 84 patients in chronic phase (CP) at baseline, 26 (31%) switched to bosutinib due to resistance and 57 (68%) due to intolerance to prior TKIs. Cumulative complete cytogenetic and major molecular response rates in CP patients were 67% and 55%, respectively. After a median follow‐up of 21.5 months, nine (11%) patients in CP died; estimated overall survival rates at 1 and 2 years postbosutinib initiation were 95% and 91%, respectively. Overall, 33/87 (38%) patients discontinued bosutinib due to either lack of efficacy/disease progression (17%), adverse events (14%), death (2%), or other reasons (5%). Eighty‐two (94%) patients experienced ≥1 adverse event possibly related to bosutinib, most commonly diarrhea (52%). Conclusions: Bosutinib used in routine clinical practice in heavily pretreated patients with CML is an effective treatment for patients in CP and is generally tolerable.